Desenvolvimento da cultura surda no currículo de escolas bilíngues para surdos: a fala de professores surdos - Nakasato, Ricardo Quiotaca (2019)
This master's dissertation, conducted by a Deaf researcher - Ricardo Nakasato, focuses on the contextualization of Sign Language, Deaf Culture, curriculum and bilingual education, with a view to understanding the bilingual curriculum as a possibility for the development of Culture Deaf at school, so as to critically point out the role of the deaf teacher in this process. Through the study concerning the theoretical parameters of different authors on the theme, a parallel is drawn with the socio-cultural presuppositions and the anthropological view of deafness, seeking to point out essential characteristics for the constitution of the Deaf Being as subjects full of rights.The purpose of this research is therefore to analyze the articulations between the Deaf Culture and the school curriculum in bilingual schools for the Deaf, identifying their conceptions and implications through representations expressed in the view of Deaf teachers. Some authors were used as the theoretical basis of the research, as follows: Abramowicz (2006), Pereira (2011), Quadros e Karnopp (2004), Sacks (1998), Skliar (1998, 1999), among others. Through a qualitative methodology, the field research was developed through the interviews with four Deaf teachers who work in a bilingual school in order to understand their practices and their critical positioning in relation to the school curriculum, considering their relation with the Culture Deaf